2013
DOI: 10.1177/2158244013510305
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Latent Factor Structure of the MSLQ

Abstract: The Motivated Strategies for Learning Questionnaire (MSLQ) has a long history of use in educational psychology, yet few studies have examined the latent factor structure of the entire scale using data from a single administration of the instrument. Although using the subscales individually was encouraged by the creators of the instrument, the practice has produced piecemeal evidence for the latent factor structure. In the current study, we administered all 15 subscales of the MSLQ to a large population of post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 22 publications
2
33
0
9
Order By: Relevance
“…Sample items included "When work is difficult I either give up or study only the easy parts", and all items on this measure have demonstrated adequate reliability in prior research (Hilpert, Stempien, van der Hoeven, & Husman, 2013;Pintrich et al, 1993) and in the present study (ω = .74). With regards to the CFA, residual correlation between two of the four items that were worded in a similar way was allowed, the χ 2 value and fit indexes were χ 2 (1402, 1) = 3.05 (p = .08), RMSEA = .04 [.00, .09], CFI = .99, TLI = .99.…”
Section: Effort Regulationmentioning
confidence: 86%
See 1 more Smart Citation
“…Sample items included "When work is difficult I either give up or study only the easy parts", and all items on this measure have demonstrated adequate reliability in prior research (Hilpert, Stempien, van der Hoeven, & Husman, 2013;Pintrich et al, 1993) and in the present study (ω = .74). With regards to the CFA, residual correlation between two of the four items that were worded in a similar way was allowed, the χ 2 value and fit indexes were χ 2 (1402, 1) = 3.05 (p = .08), RMSEA = .04 [.00, .09], CFI = .99, TLI = .99.…”
Section: Effort Regulationmentioning
confidence: 86%
“…Sample items include "I try to play around with ideas of my own related to what I am learning", and this measure has been reliable in previous work (Hilpert et al, 2013;Pintrich et al, 1993) and the present study (ω = .84). With regards to the CFA, the χ 2 value and fit indexes were χ 2 (1403, 2) = 19.85 (p = .00), RMSEA = .08 [.05, .11], CFI = .99, = .99.…”
Section: Deep-processingmentioning
confidence: 87%
“…Al retomar el tema del volumen de producción asociado al MSLQ, se constata otro conjunto de estudios en los que se han analizado las propiedades psicométricas de este instrumento (Pintrich et al, 1993;Hilpert et al, 2013;Dunn, Lo, Mulvenon, & Sutcliffe, 2012); de modo sistemático este instrumento ha mostrado ser una me-dida confiable de la motivación y las estrategias de aprendizaje autorregulado. Como lo señalaran Duncan y McKeachie (2005), el MSLQ se caracteriza por poseer una estructura conceptual sólida que brinda sustento a su construcción.…”
Section: Introductionunclassified
“…Sin embargo, también cabe mencionar que varios estudios han informado problemas vinculados a la estructura factorial latente y han sugerido importantes modificaciones. En particular Hilpert et al (2013), tras reespecificar la estructura factorial del MSLQ, y luego de explorar varios modelos mediante análisis factorial confirmatorio, propusieron remover más de la mitad de las subescalas, de modo que el modelo final quedó compuesto por tres factores con dos subescalas cada uno: expectativa (autoeficacia y control del aprendizaje), valor (metas intrínsecas y valor de la tarea) y autorregulación (regulación metacognitiva y regulación del esfuerzo).…”
Section: Introductionunclassified
“…The items that were developed for operationalizing these constructs later formed the basis for the 15 subscales mentioned above. MSLQ has been applied in many research studies (Duncan and McKeachie 2005), partly aiming at developing a new conceptualization with respect to the significance of the single sub-scales (Dunn et al 2012;Hilpert et al 2013). MSLQ's reliability has proved "robust", and its predictive validity to actual course performance is considered "reasonable" (Pintrich et al 1993, p. 801).…”
Section: Questionnaires For Assessing Learning Strategiesmentioning
confidence: 99%